Multicomponent biosurfactants--A "Green Toolbox" extension - Jirku, Vladimir; Cejkova, Alena; Schreiberova, Olga; Jezdik, Richard; Masak, Jan (Biotechnology advances, 2015)
The unflagging interest in the surfactants of biological origin, representing ecological alternatives to their synthetic counterparts, has enhanced R&D effort both to produce their new types and to resolve the bottlenecks of their commercialization. In this context, the rhamnolipids, offering a relatively large scale of potential applications, variety of congeners, low toxicity as well as stability towards the extremes of environment, logically attract attention. In this connection, the current state of knowledge concerning these compound exploitation, biosynthesis control and non-genetic factors affecting both production yield and final rhamnolipid product is surveyed.
Keywords: biokompatibilní materiály; Biocompatible Materials; Surface-Active Agents; glykolipidy; Glycolipids; povrchově aktivní látky